Tunable controlling the retrogradation rate of wheat starch using different fractions of Artemisia sphaerocephala Krasch polysaccharide. (November 2021) - Zhang, Kailong; Li, Xiaowen; Li, Junjun; Wang, Xiaolong; Ren, Tian; Ma, Zhen; Li, Xiaoping; Hu, Xinzhong
Abstract: The gelatinization and retrogradation of wheat starch (WS) with the addition of Artemisia sphaerocephala Krasch polysaccharide (ASKP) and its two fractions, i.e., the high molecular weight fraction (60P) and the low molecular weight fraction (60S), are investigated. RVA results demonstrated that the setback viscosities of WS increased after the addition of ASKP or 60P, suggesting ASKP or 60P could accelerate the short-term retrogradation of WS. Whereas 60S showed the adverse effect. Dynamic rheological measurements indicated that the G′ value increased with the addition of ASKP or 60P, but decreased with that of 60S. DSC and XRD results indicated that ASKP, 60P, and 60S had an inhibition effect on the long-term retrogradation of WS. ASKP or 60P increased the firmness of gel at the beginning stage but decreased it after long-term storage. However, 60S weakened the gel firmness throughout the whole process. ASKP, 60P, and 60S showed various modulating effects on the retrogradation rate of WS. This work provides an experimental basis for controlling the retrogradation rate of wheat starch by selecting different fractions of ASKP. Highlights: Inhibition of ASKP and its two fractions on starch retrogradation were investigated. ASKP and 60P can accelerate short-term whereas decelerate long-term retrogradation. Low Mw fraction of ASKP (60S) could inhibit retrogradation of wheat starch. Selecting different ASKP fractions enables a tunable starch retrogradation rate.